2011
DOI: 10.1007/s11434-011-4607-8
|View full text |Cite
|
Sign up to set email alerts
|

Interannual and interdecadal variations in the North Atlantic Oscillation spatial shift

Abstract: The spatial shift of the North Atlantic Oscillation (NAO) is analyzed by using the Twentieth Century Reanalysis version 2 dataset and identifying NAO action centers directly on winter mean sea-level pressure (SLP) anomaly maps. The spatial shift of the NAO is characterized by four NAO spatial shift indices: the zonal and meridional shifts of the NAO southern and northern action centers. It is found that the zonal and meridional shift trends of the NAO action centers move along a path of southwest-northwest dir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 35 publications
(46 reference statements)
2
38
0
Order By: Relevance
“…5). The former most probably reflects the rhythm of atmospheric circulation in the North Atlantic (North Atlantic Oscillation), while the latter reflects the impact of ocean circulation associated with the AMO (Atlantic Multidecadal Oscillation) mechanism (Schlesinger and Ramankutty 1994;Enfield et al 2001;Portis et al 2001;Zhang et al 2011). Similar relationships have been identified in the case of multi-annual changes in air temperature in the Karkonosze range (Migała et al 2015).…”
Section: Characteristics Of Sunshine Duration and Trendsmentioning
confidence: 99%
“…5). The former most probably reflects the rhythm of atmospheric circulation in the North Atlantic (North Atlantic Oscillation), while the latter reflects the impact of ocean circulation associated with the AMO (Atlantic Multidecadal Oscillation) mechanism (Schlesinger and Ramankutty 1994;Enfield et al 2001;Portis et al 2001;Zhang et al 2011). Similar relationships have been identified in the case of multi-annual changes in air temperature in the Karkonosze range (Migała et al 2015).…”
Section: Characteristics Of Sunshine Duration and Trendsmentioning
confidence: 99%
“…The 15.9‐year and 18.6‐year quasiperiods of reconstructed precipitation were approximate to the interdecadal changes of NAO (Fu and Zeng, ). In addition, NAO also has interannual periodicities (Zhang et al, ). Wavelet coherence analysis (Figure ) showed that the reconstructed precipitation had some similar cycles as the NAO cycles at interannual and interdecadal time scales.…”
Section: Discussionmentioning
confidence: 99%
“…Since long time variability is significant in both the Indo-Pacific SST and the SAH (Zhang et al 2000;Du and Xie 2008), the data have been detrended to eliminate the contribution of trends to the statistical results. Unless stated, the detrending is performed on the data of each target period, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…3, except for JJA SST preceding winter after the late-1970s Qu and Huang 2012;Yang et al 2007;Zhang et al 2000).…”
Section: Influence Of the Indo-pacific Sst On The Sahmentioning
confidence: 99%
See 1 more Smart Citation